A study of library software systems in academic libraries in Metro Manila - Cornago, Pia Charmaine F. (2003)
This study made use of the three library software systems (Athena, Follett and MaeLisa) to determine whether additional training of librarians on their applications could improve the software systems' performance. The descriptive method was used with a survey questionnaire as the main-gathering tool. Data from the websites of the software vendors supplemented the responses of one hundred twenty (120) professional librarians, eleven (11) head librarians and eleven (11) system administrators, or a total of one hundred forty-two (142) respondents of the survey. They are from eleven (11) colleges and universities that were provided by the three software systems' distributors.